Pengaruh AI Literacy, Digital Marketing, dan Differentiation Strategy terhadap Competitive Advantage pada UMKM Donatsu di Kota Bandung - Afrian Insan Kamil; Ai Malita Wulandari; Intan Nur’aini; Megha Sakova (INDO PUBLISHING, 2026)
This study aims to analyze the influence of AI Literacy, Digital Marketing, and Differentiation Strategy on Competitive Advantage among Donatsu, a culinary micro, small, and medium-sized enterprise (MSME) in Bandung City. A quantitative associative approach was employed using purposive sampling on 64 respondents who were Donatsu consumers in East Bandung. Data were collected through a five-point Likert-scale questionnaire and analyzed using multiple linear regression with IBM SPSS Statistics, following validity and reliability testing. The results show that, partially, AI Literacy (Sig. = 0.899) and Digital Marketing (Sig. = 0.606) have no significant effect on Competitive Advantage, whereas Differentiation Strategy has a positive and significant effect (B = 0.928; Sig. < 0.001) and emerges as the dominant variable. Simultaneously, the three variables significantly affect Competitive Advantage (F = 239.663; Sig. < 0.001), with an Adjusted R Square of 0.919, indicating that 91.9% of the variance in Competitive Advantage can be explained by these three variables. These findings suggest that AI literacy and digital marketing currently function merely as hygiene factors in the culinary competitive landscape, while product uniqueness and customer experience serve as the primary sources of sustainable competitive advantage for MSMEs. This study recommends that Donatsu prioritize investment in strengthening product and service differentiation rather than solely advancing promotional technology.